Comparison of Mean Weight, Length and Head Circumference in Preterm Neonates with Zinc Supplement Group Versus without Zinc Supplement Group - Zunera Riaz Cheema, Aleena Asif, Nazia Zaib, Irsa Iqbal, Sana Jamil, Zia Ur Rehman Zia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare mean weight, length and head circumference in preterm neonates with zinc supplement group versus without zinc supplement group. Design of the Study: Randomized controlled trial Study Settings: The study was carried out in the Pediatric Department of Lahore General Hospital Lahore from February 2021 to July 2021. Material and Methods: There were two groups of babies: one that received Zinc supplementation and one that did not (not treated with Zinc supplements). An electronic weighing scale was used to measure weight prior to intervention. Mothers were given two bottles of supplement containing zinc when their newborns were 7 to 21 days old, before being discharged from the hospital, and encouraged to feed their babies orally at a dose of 2 mg/kg/day with other multivitamins for six weeks (study group). For the same period of time, the participants in the control group were advised to take only multivitamins. Additionally, anthropometric measurements such as weight, height, and head circumference were taken. Results of the Study: In our study, mean age was calculated as 33.74+1.36 weeks in study and 33.64+1.38 weeks in control group, 54.76%(n=23) in study and 59.52%(n=25) in control group were male while 45.24%(n=19) in study and 40.48%(n=17) in control group were females Conclusion: Preterm neonates supplemented with zinc were significantly better than those without zinc supplementation with regards to mean weight, length and head circumference